2008
DOI: 10.1063/1.3020298
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation photoemission spectroscopic study of band offsets and interface self-cleaning by atomic layer deposited HfO2 on In0.53Ga0.47As and In0.52Al0.48As

Abstract: whereas in-situ vacuum annealing removes surface arsenic pile-up. After the atomic layer deposition of HfO 2 , native oxides were considerably reduced compared to that in as-received epi-layers, strongly suggesting the self-clean mechanism. Valence and conduction band offsets are measured to be 3.37±0.1eV, 1.80±0.3eV for In 0.53 Ga 0.47 As and 3.00±0.1eV, 1.47±0.3eV for In 0.52 Al 0.47 As, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 17 publications
1
26
0
3
Order By: Relevance
“…The sample treated with the ex situ aqueous ͑NH 4 ͒ 2 S solution has the thickest IL ͑1.3 nm͒ of all the In 0.53 Ga 0.47 As samples which experience a surface treatment prior to HfO 2 ALD growth. The untreated In 0.53 Ga 0.47 As sample has an IL oxide thickness of 1.9 nm and is comparable to the native oxide thickness of 2 nm found on In 0.53 Ga 0.47 As by Kobayashi et al 12 A number of recent publications have demonstrated that ALD deposition of Al 2 O 3 ͓using Al͑CH 3 ͒ 3 ͔ and HfO 2 ͕using Hf͓N͑CH 3 ͒ ϫ͑C 2 H 5 ͔͒ 4 ͖ on GaAs and In x Ga 1−x As substrates can reduce the thickness of interfacial Ga and As oxides during the ALD growth process. 6,7,12,13 This is referred to as an interfacial "self-cleaning process" and is most likely precursor dependent.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…The sample treated with the ex situ aqueous ͑NH 4 ͒ 2 S solution has the thickest IL ͑1.3 nm͒ of all the In 0.53 Ga 0.47 As samples which experience a surface treatment prior to HfO 2 ALD growth. The untreated In 0.53 Ga 0.47 As sample has an IL oxide thickness of 1.9 nm and is comparable to the native oxide thickness of 2 nm found on In 0.53 Ga 0.47 As by Kobayashi et al 12 A number of recent publications have demonstrated that ALD deposition of Al 2 O 3 ͓using Al͑CH 3 ͒ 3 ͔ and HfO 2 ͕using Hf͓N͑CH 3 ͒ ϫ͑C 2 H 5 ͔͒ 4 ͖ on GaAs and In x Ga 1−x As substrates can reduce the thickness of interfacial Ga and As oxides during the ALD growth process. 6,7,12,13 This is referred to as an interfacial "self-cleaning process" and is most likely precursor dependent.…”
Section: Methodsmentioning
confidence: 49%
“…The untreated In 0.53 Ga 0.47 As sample has an IL oxide thickness of 1.9 nm and is comparable to the native oxide thickness of 2 nm found on In 0.53 Ga 0.47 As by Kobayashi et al 12 A number of recent publications have demonstrated that ALD deposition of Al 2 O 3 ͓using Al͑CH 3 ͒ 3 ͔ and HfO 2 ͕using Hf͓N͑CH 3 ͒ ϫ͑C 2 H 5 ͔͒ 4 ͖ on GaAs and In x Ga 1−x As substrates can reduce the thickness of interfacial Ga and As oxides during the ALD growth process. 6,7,12,13 This is referred to as an interfacial "self-cleaning process" and is most likely precursor dependent. The thickness of the IL oxide for the untreated sample ͑1.9 nm͒ indicates that limited or no interfacial self-cleaning process is occurring using the Hf͓N͑CH 3 ͒ 2 ͔ 4 and H 2 O water process.…”
Section: Methodsmentioning
confidence: 49%
“…The possible reasons for a higher level of charge trapping in the p-type sample compared to the n-type sample are: (i) a higher density of border traps with energy levels aligned with the In 0.53 Ga 0.47 As valance band edge than that aligned with the conduction band edge, (ii) the barrier height DE v for the trapped holes to be removed from the border traps is larger than the barrier height DE c for the trapped electrons. 33 The study of the C-V hysteresis also included an examination of the impact of the metal gate based on low (i.e., aluminium) and high (i.e., platinum) work function metals, as detailed in Table I. Figure 4 shows the C-V hysteresis for the Pt/HfO 2 (5 nm)/n-In 0.53 Ga 0.47 As and Al/HfO 2 (5 nm)/n-In 0.53 Ga 0.47 As MOS capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…Energy barriers at interfaces between "100… In x Ga 1−x As "0 Յ x Յ 0.53… and atomic-layer deposited Al 2 The electron energy band alignment at interfaces of In x Ga 1−x As ͑0 Յ x Յ 0.53͒ with atomic-layer deposited insulators Al 2 O 3 and HfO 2 is characterized using internal photoemission and photoconductivity experiments. The energy of the In x Ga 1−x As valence band top is found to be only marginally influenced by the semiconductor composition.…”
mentioning
confidence: 99%